Curcumin mitigates polycystic ovary syndrome in mice by suppressing TLR4/MyD88/NF-κB signaling pathway activation and reducing intestinal mucosal permeability - Qin Yang; Qin Wan; Zhen Wang (Scientific Reports)
Abstract Polycystic ovary syndrome (PCOS) is an endocrine-metabolic disorder closely associated with chronic inflammation. Curcumin, a polyphenolic lipophilic compound, has been shown to improve the intestinal mucosal barrier and reduce low-grade systemic inflammation. This study aimed to assess the effects of curcumin on attenuation of PCOS in a mouse model and to explore the underlying mechanisms involved. C57BL/6J mice were divided into 4 groups (n = 15 per group): CON: control group, CON/CUR: CON with curcumin group, MOD: model group, MOD/CUR: MOD with curcumin group. The MOD and MOD/CUR groups were injected with dehydroepiandrosterone (DHEA) (6 mg/100 g BW) dissolved in soybean oil to induce a PCOS-like state. After curcumin intervention (200 mg/kg) for 45 days, the mice were euthanized for analysis of various physiological and biochemical parameters. In MOD/CUR group, significant decreases in body weight (BW) (p = 0.0254), testosterone (T) levels (p = 0.0052), luteinizing hormone (LH) levels (p = 0.0438), and the LH/follicle-stimulating hormone (FSH) (p = 0.0271) levels were observed, while estradiol (E2) (p = 0.0415) level and insulin sensitivity (p = 0.0441) were increased. Histological examination (HE) staining of ovarian and colon tissues showed that curcumin ameliorated both PCOS-associated morphological changes and colon tissue pathology. Western blot and immunohistochemistry analyses of colon tissues revealed increased levels of tight junction proteins, ZO-1 (Western blot, p = 0.0360; immunohistochemistry, p = 0.0273) and occluding (Western blot, p = 0.0189; immunohistochemistry, p = 0.0224) in the MOD/CUR group. Additionally, inflammatory indicators from plasma and ovary, including IL-17 A (plasma, p = 0.0120; ovary, p = 0.0414), IL-6 (plasma, p = 0.0344; ovary, p = 0.0379), TNF-α (plasma, p = 0.0078; ovary, p = 0.0488), and lipopolysaccharides (LPS) (plasma, p = 0.0144), were decreased, while IL-10 (plasma, p = 0.0270; ovary, p = 0.0267) was increased in MOD/CUR group. The levels of NF-κB p65 (p = 0.0229), TLR-4 (p = 0.0462) and MyD88 (p = 0.0152) in ovarian tissues were significantly increased in MOD/CUR group. Our results revealed that curcumin alleviates PCOS by inhibiting TLR4/MyD88/NF-κB signaling pathway activation and reducing intestinal mucosal permeability. These findings suggest that curcumin may provide a potential clinical approach for managing PCOS.